Consumer Perception For E-Banking Technology - A Survey Of Consumers In Klang Valley - Baharin, Adilah (2005)
The purpose of this study is to determine and to increase our current understanding of the factors that influence online banking acceptance. More precisely, online banking acceptance will be studied from the information systems acceptance point of view referring to the idea that consumers are using banks information system (online banking service directly and hence more knowledge on the factors that affect information systems adoption is needed in order to better understand and facilitate the acceptance.